As medidas de higiene mental propostas por Luiz Antonio dos Santos Lima e a Legislação Educacional Norte-Rio-Grandense (1889-1930) - Silva, Juliana da Rocha e (2017)
This research relates the school hygiene measures proposed by Luiz Antonio dos Santos Lima, a Brazilian educator and physician, in “Mental Hygiene and Education” (1927b), to the Rio Grande do Norte’s educational law of 1889-1930. For this, we developed the thesis that the hygiene discourse defended by Luiz Antonio, aimed at mental hygiene of schoolchild, shows an innovative aspect when related to the hygiene measures present in educational law of that period, still focused on the bodies cleanliness and structure of school buildings. It is a documentary and bibliographic research that studies “Mental Hygiene and Education”, a doctoral thesis published in 1927, and law, decrees, government messages, school reforms and director of public education’s reports, dated from 1889 to 1930, with regard to school hygiene policy. For analysis and interpretation of the sources, we use the Foucauldian discourse analysis, which help us to understand that the documents we analysed were based on a medical-scientific knowledge and produced a discourse of truth which aimed to control, correct and monitor the bodies of schoolchildren. In addition, we are based on Canguilhem’s theory to understand how medical knowledge imposed the normal and abnormal patterns of life, with Medicine ceasing to be the art of healing to become the science of disease. We realized that the doctoral thesis and the educational law from 1889 to 1930 emphasize the need for complete education – physical, intellectual and moral – of the child, whose formation would be directly conditioned to the hygiene measures to be implemented in school environment. The hygiene measures analyzed in the research sources are complementary as they bring different paths to achieve the same educational desire and to show the sides of a same coin that was based on the influence of Medicine in Education. We believe the concept of hygiene defended by Luiz Antonio dos Santos Lima presented an innovative aspect when it emphasizes the mental characteristics of each schoolchild. The Brazilian educator explains in detail how educational practice should prevent, correct and control every schoolchild mental deviation. Thus, we can conclude that Luiz Antonio dos Santos Lima’s educational thought was a new milestone for the social hygiene movement defended in Rio Grande do Norte state.